Overexpression of oHIOMT results in various morphological, anatomical, physiological and molecular changes in switchgrass - Huang, Yanhua; Lai, Xianzhi; Liu, Changfa; Zhu, Wentao; Hao, Yongren; Zheng, Zehui; Guo, Kai (Frontiers in Plant Science, 2024)
Introduction Melatonin (N-acetyl-5-methoxytryptamine) is a molecule implicated in multiple biological functions, but exerts contrasting effects on plants owing to concentration differences. Hydroxyindole O-methyltransferase (HIOMT), which catalyzes the last step of melatonin synthesis, plays a crucial role in this context. Methods Transgenic switchgrass overexpressing oHIOMT with different melatonin levels displayed distinct morphological changes in a concentration-dependent manner. In this study, we divided the transgenic switchgrass into two groups: melatonin-moderate transgenic (MMT) plants and melatonin-rich transgenic (MRT) plants. To determine the concentration-dependent effect of melatonin on switchgrass growth and stress resistance, we conducted comparative morphological, physiological, omics and molecular analyses between MMT, MRT and wild-type (WT) plants. Results We found that oHIOMT overexpression, with moderate melatonin levels, was crucial in regulating switchgrass growth through changes in cell size rather than cell number. Moderate levels of melatonin were vital in regulating carbon fixation, stomatal development and chlorophyll metabolism. Regarding salt tolerance, melatonin with moderate levels activated numerous defense (e.g. morphological characteristics, anatomical structure, antioxidant enzymatic properties, non-enzymatic capacity and Na+/K+ homeostasis). Additionally, moderate levels of oHIOMT overexpression were sufficient to increase lignin content and alter monolignol compositions with an increase in the S/G lignin ratio. Discussion Taken together, oHIOMT overexpression in switchgrass with different melatonin levels resulted in morphological, anatomical, physiological and molecular changes in a concentration-dependent manner, which characterized by stimulation at low doses and inhibition at high doses. Our study presents new ideas and clues for further research on the mechanisms of the concentration-dependent effect of melatonin.